EFISIENSI SERAPAN UNSUR 15N-UREA DAN PROPORSI FIKSASI N OLEH TANAMAN KEDELAI TIDAK BERKOTILEDON PADA BUDIDAYA JENUH AIR - Avivi, Sholeh; Mugnisjah, Wahju Q.; Idris, Komarudin; Sisworo, Elsye L. (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
This pot experiment was to evaluate the influences of cotyledons detachment at seedling stage on the efficiency of labelled N-urea uptake and proportion of N-fixation by soybean cv. Wilis grown under saturated soil culture. Based on the result of preliminary experiment, cotyledons detachment was held at 7 days after sowing (das). The cotyledons detachment significantly reduced N-urea uptake efficiency and N-fixed proportion. The N-urea uptake efficiency at 21 days, R4, R5, R6, and R8 stages by cotyledons-detached plant were 30.5 %, 24.6 %, 23.7 %, 24.0 %, and 22.45 of the total N assimilated. Those of the cotyledons undetached-plant (control plant), the value were 31.6 %, 24.05, 24.7 %, 2.7 %, and 23.6 % respectively. At R8 stage, the cotyledons-detached plant has the amount of N-fixed proportion of 54.2 and N-soil of 23.4 %, whereas those of the control one had the amount of 49.7 and 26.7 % respectively. N-urea uptake, N-fixed, and N-soil uptake by the cotyledons- detached plant were lower than that of the control one (i.e. 69, 80, and 645 of the control respectively). The cotyledons detachment also result in inferior vegetative and productive growth of the plant in terms of decreased root dry weight (21.1 %), leave dry weight (18.8 %), plant dry weight (26.7 %), pot dry weight (23.8 %), grain number/pot (32.8 %), and grain dry weight (26.9 %). It seems that the lower growth and yield of the cotyledons-detached soybean paint were caused by the lower total N-uptake due to cotyledons detachment.